Fenestrated Thoracic Endovascular Aortic Repair Using Physician Modified Stent Grafts for Acute Type B Aortic Dissection with Unfavourable Landing Zone. (February 2018) - Zhu, Jiechang; Zhao, Lujing; Dai, Xiangchen; Luo, Yudong; Fan, Hailun; Feng, Zhou; Zhang, Yiwei; Hu, Fanguo
Abstract : Objectives: The aim was to evaluate the early results of fenestrated thoracic endovascular aortic repair (fTEVAR) using physician modified stent grafts (PMSGs) to revascularise aortic branches for acute type B aortic dissection (ABAD) with unfavourable proximal landing zone. Methods: Twenty consecutive patients who underwent fenestrated TEVAR using PMSGs between November 2015 and December 2016 were retrospectively reviewed. Pre-, intra-, and post-operative clinical data were recorded. Results: The median patient age was 53 years (range, 18–83 years), and 16 of the 20 (80%) patients were men. Indications were complicated ABAD with unfavourable proximal landing zones, including inadequate proximal landing zone ( n  = 4), retrograde dissection extending to the left subclavian artery (LSA) ( n  = 13), and retrograde haematoma involving the LSA ( n  = 3). Twenty PMSGs (Medtronic Valiant stent grafts, n  = 4; Relay thoracic stent grafts, n  = 10; Ankura thoracic stent grafts, n  = 6) were deployed. One LSA fenestration was created in 19 patients, and one LSA fenestration combined with a left common carotid artery (LCCA) scallop was created in one patient. Branch stents consist of a covered stent for the LSA ( n  = 7), an uncovered stent for the LSA ( n  = 14), and an uncovered stent for the LCCA ( n  = 1). The median duration for stent graft modifications was 40 min (range 30–60 min). The mean interval between symptom onset and treatment was 5 ± 3 days (range, 1–10 days). The initial technical success rate was 90% (18 of 20). Partial coverage of the LCCA in one patient resolved after uncovered chimney stent implantation in the LCCA. Type III endoleak between the LSA covered stent and the PMSG occurred in this patient 1 week post fTEVAR and resolved after re-intervention with deployment of an Amplatzer occluder device across the site of the leak. A chimney stent was deployed to solve the misalignment of the LSA in another patient. The mean operation time was 101 ± 48 min, and fluoroscopy time was 24 ± 16 min. There were no in hospital deaths and no peri-operative neurological complications. The median length of stay was 9 ± 6 days (range, 5–26 days). One patient had a left brachial artery (LBA) pseudoaneurysm at the puncture site that required open repair. One patient presented renal deterioration post-operatively and recovered uneventfully after conservative therapy. All patients survived at a mean follow-up of 6.95 months (range, 2–14 months). During follow-up, no post-operative complications occurred and all target vessels remained patent. No fenestration related Type I or III endoleaks were observed. Conclusions: fTEVAR using PMSGs may be a viable alternative for patients who present with ABAD without healthy proximal landing zones and who are unable to wait for a custom made fenestrated device.